Α‐hemolysin of Staphylococcus aureus impairs thrombus formation. (27th March 2022) - Jahn, Kristin; Handtke, Stefan; Palankar, Raghavendra; Kohler, Thomas P.; Wesche, Jan; Wolff, Martina; Bayer, Janina; Wolz, Christiane; Greinacher, Andreas; Hammerschmidt, Sven
Abstract: Background: Toxins are key virulence determinants of pathogens and can impair the function of host immune cells, including platelets. Insights into pathogen toxin interference with platelets will be pivotal to improve treatment of patients with bacterial bloodstream infections. Materials and Methods: In this study, we deciphered the effects of Staphylococcus aureus toxins α‐hemolysin, LukAB, LukDE, and LukSF on human platelets and compared the effects with the pore forming toxin pneumolysin of Streptococcus pneumoniae . Activation of platelets and loss of platelet function were investigated by flow cytometry, aggregometry, platelet viability, fluorescence microscopy, and intracellular calcium release. Thrombus formation was assessed in whole blood. Results: α‐hemolysin (Hla) is known to be a pore‐forming toxin. Hla‐induced calcium influx initially activates platelets as indicated by CD62P and αIIbβ3 integrin activation, but also induces finally alterations in the phenotype of platelets. In contrast to Hla and pneumolysin, S. aureus bicomponent pore‐forming leukocidins LukAB, LukED, and LukSF do not bind to platelets and had no significant effect on platelet activation and viability. The presence of small amounts of Hla (0.2 µg/ml) in whole blood abrogates thrombus formation indicating that in systemic infections with S .  aureus the stability of formed thrombi is impaired. Damage of platelets by Hla was not neutralized by intravenous immune globulins. Conclusion: Our findings might be of clinical relevance for S .  aureus induced endocarditis. Stabilizing the aortic‐valve thrombi by inhibiting Hla‐induced impairment of platelets might reduce the risk for septic (micro‐)embolization.